1981
DOI: 10.1073/pnas.78.5.3118
|View full text |Cite
|
Sign up to set email alerts
|

Differential activity of DNA methyltransferase in the life cycle of Chlamydomonas reinhardi.

Abstract: Two molecular weight. forms of DNA (cytosine-5-)-methyltransferase [S-adenosyl-L-methionine:DNA (cytosine-5-)-methyltransferase, EC 2.1.1.37], both active in assays in vitro, were isolated from the green alga Chlamydomonas reinhardi at various stages of the life cycle. The enzyme with Mr 60,000 was found in vegetative cells and gametes of both male (mtF) and female (mtt) mating types. The enzyme with Mr 200,000 was specific to gametic cells and zygotes, which are the only stages at which methylation of chlorop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…For example, selective methylation of chloroplast DNA has been consistently observed in mt ϩ gametes with buoyant density centrifugation (13), restriction enzyme cleavage patterns (6), and by southwestern hybridization with anti-m 5 C antibodies (3). A gamete-and zygote-specific DNA methyltransferase with a high molecular mass also was identified (20). However, the evidence was indirect, and critical experiments showing a direct association of methylation with persistence of mt ϩ chloroplast DNA during mating have hitherto not been performed to our knowledge.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, selective methylation of chloroplast DNA has been consistently observed in mt ϩ gametes with buoyant density centrifugation (13), restriction enzyme cleavage patterns (6), and by southwestern hybridization with anti-m 5 C antibodies (3). A gamete-and zygote-specific DNA methyltransferase with a high molecular mass also was identified (20). However, the evidence was indirect, and critical experiments showing a direct association of methylation with persistence of mt ϩ chloroplast DNA during mating have hitherto not been performed to our knowledge.…”
Section: Discussionmentioning
confidence: 95%
“…In our previous study, we identified a mt ϩ gamete-and zygote-specific DNA methyltransferase of Ϸ200 kDa, which methylates both unmethylated and hemimethylated chloroplast DNA (20). Its identity may in fact be CrMET1, given the molecular mass of Ϸ150 kDa, and the mt ϩ gamete specificity.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, DNA methylation controls the transcriptional activity of certain algal genes. Site-specific DNA methyltransferases in Chlamydomonas have been isolated and characterized (Sano & Sager, 1980;Sano et al, 1981). In Chlamydomonas, chloroplast genes are maternally inherited.…”
Section: (B) Non-virus Eukaryotic Systemsmentioning
confidence: 99%
“…Several methyltransferase enzymes that modify cpDNA have been investigated biochemically (Sano et al, 1981), and one candidate chloroplast methyltransfersase gene has been cloned (Nishiyama et al, 2002(Nishiyama et al, , 2004. Since that time, the genome sequence of C. reinhardtii has become available (Merchant et al, 2007) and extensively annotated so that a comprehensive identification of genes encoding DNA methyltransferases can be undertaken.…”
mentioning
confidence: 99%